Drivers of damselfishes distribution patterns in the southwestern Atlantic: tropical and subtropical reefs compared - Chaves,Laís de C. T. (2021)
Abstract Damselfishes are known keystone species of reef environments, however large-scale distribution patterns are poorly studied in the southwestern Atlantic. We evaluated main drivers of distribution of three conspicuous damselfishes, along tropical and subtropical coastal systems, in Brazil. Abundances were assessed against wave exposure, depth (within 1–7 m in tropical and 1–11 m in subtropical reefs) and benthic cover. Despite differences between systems, exposure and depth consistently explained damselfishes distribution. Stegastes fuscus, the larger damselfish species of the genus in the southwestern Atlantic, was dominant in both systems, inhabiting preferably shallow and sheltered reefs. Conversely, Stegastes variabilis occupied shallow habitats with higher exposure. Stegastes pictus was absent from tropical reefs sampled, inhabiting depths >7 m, in subtropical reefs. Species were weakly associated with benthic features, which poorly predicted changes in abundances. Regardless, S. fuscus showed association with articulated calcareous algae, and S. variabilis juveniles associated with erect macroalgae. Despite occurring in very distinctive reef systems, Brazilian damsels habitat requirements are consistent in both tropical and subtropical reefs. While highly persistent species, long term monitoring will inform us how they respond to pervasive global changes and human impacts along Brazilian reefs.